The Influence of Language in Forming Political Identity in Indonesia - Hoerudin, Cecep Wahyu (Global Writing Academica Researching & Publishing, 2024)
Language plays a significant role in shaping political identity in Indonesia from the colonial period to the reform era. The use of language in politics, campaigns, and social media shows how language shapes political narratives and mobilizes support. Language policy faces challenges in managing linguistic diversity while maintaining social and political stability. This study aims to analyze the role of language in Indonesian politics and its impact on political identity and social cohesion. This study uses a qualitative approach by collecting data from various relevant sources, such as previous research results. The collected data is then processed through qualitative analysis to find research results. The results of this study found that language plays a significant role in building political identity and mobilizing support in Indonesia. The use of Indonesian and regional languages ​​creates a balance between national unity and local identity. Social media and political campaigns use language to influence public opinion and strengthen political narratives. Language policies that are inclusive and responsive to linguistic diversity can support social cohesion and equitable national development. This study provides insight into the importance of language in the dynamics of Indonesian politics and offers recommendations for more inclusive policies.